DECISION MAKING FOR MARKETING STRATEGIES PT ZXC FOR PT QWE’S PRODUCT IN INCREASING SALES WITH AHP - Adam Riztama Amora; Pri Hermawan (CV. Radja Publika, 2025)
Using the Analytic Hierarchy Process (AHP) method, this study attempts to find and evaluate efficient marketing methods to boost sales of Dosing Pump products from PT QWE through PT ZXC. Particularly for PT QWE items that contribute significantly to the company's revenue, PT ZXC's sales have stalled over the last five years. The nationwide demand for products with HS code 8413.50.90 has increased despite a decline in purchases from PT ZXC, suggesting fierce rivalry at the supplier level. The primary target markets were determined by historical data analysis and AHP to be businesses with high purchase frequency and value, such as oil and gas, power plants, water/wastewater, and petrochemicals. The Technical Workshop Masterclass was the most successful marketing technique, according to the AHP statistics, because it was relevant to the target market and improved product comprehension. It is therefore recommended that PT ZXC concentrate on setting up technical workshops, expanding its target market, and enhancing its after-sales support. To guarantee long-term efficacy, marketing techniques should also be periodically reviewed and modified in response to consumer input. It is anticipated that PT ZXC will boost sales of PT QWE products and solidify its place in the cutthroat industry with this approach.